Epidemiology of fractures and dislocations in children - Nugraha, Hans Kristian; Adiantono, Agus (Folia Medica Indonesiana, 2017)
Fracture is quite a common occurrence in the age group of children, with a fairly wide variety of epidemiology throughout the world, hence it could be considered as a major health problem. A retrospective study of all pediatric fractures presenting to Dr. Soegiri General Hospital Lamongan, Indonesiain 2015 was undertaken. It showed that 79.5% of children's fractures occurred in males and that 86.76% presented as a single fracture, whileelbow dislocation is the most prevalent dislocation in this study.Analysis of pediatric fractures shows that there is a trimodal distribution of single fracture with age, withdistal radius/ulna fracture as the most prevalent single fracture.The commonest cause of single fracture are road traffic accident, and the majority involve the upper limb. Those suggested that there should be more concern about road safety program in Indonesia.